Class switched bovine ultralong CDR H3 amplicons versus canonical in immune and non-immune tissues - Karina L. Hissen; Morgan Sheppard; Jeannine A. Ott; Kerstin K. Landrock; Casey Whitley; Nicholas Ebert; J. M. Cody Horton; Nicole A. Glenn; Yoonsung Jung; Vaughn V. Smider; Michael F. Criscitiello (Immunogenetics, 2026)
Within the bovine immune response, a distinct type of immunoglobulin (Ig), known as ultralong complementarity-determining region 3 (CDR3) antibodies, coexists alongside canonical Igs. These ultralong heavy chains (HC) feature a remarkable structure with a lengthened CDR3 of the heavy chain (CDR H3), allowing them to adopt either a smaller and more extended paratope than canonical antibodies. However, very little is known about the distribution of ultralong CDR H3s in cattle tissues and which isotypes they are ultimately associated with. This study analyzed and quantified the amplicons of the five immunoglobulin isotypes (IgM, IgD, IgG, IgA, and IgE) for both the canonical and ultralong CDR H3 throughout 24 Bos taurus tissues. IgH amplicons analysis identified an extensive repertoire of expressed canonical and ultralong CDR H3s of each isotype in most tissues. Ultralong cattle Igs were preferentially switched to the IgG isotype, especially in the medial retropharyngeal lymph node draining the immunization site. Additionally, B cells producing canonical Igs in bone marrow switched most to the IgG isotype. These data suggest that ultralong CDR H3 may be uniquely qualified to handle some antigens. A more comprehensive understanding of isotype and tissue-specific immune responses of these unusual antibodies can provide a deeper insight into their function within the overall cattle immune system, offering unique opportunities for innovations for in both bovine health and human immunotherapeutics.

Guidance on selecting and evaluating AI auto-segmentation systems in clinical radiotherapy: insights from a six-vendor analysis - Branimir Rusanov; Martin A. Ebert; Mahsheed Sabet; Pejman Rowshanfarzad; Nathaniel Barry; Jake Kendrick; Zaid Alkhatib; Suki Gill; Joshua Dass; Nicholas Bucknell; Jeremy Croker; Colin Tang; et al. (Physical and Engineering Sciences in Medicine, 2025)
Artificial Intelligence (AI) based auto-segmentation has demonstrated numerous benefits to clinical radiotherapy workflows. However, the rapidly changing regulatory, research, and market environment presents challenges around selecting and evaluating the most suitable solution. To support the clinical adoption of AI auto-segmentation systems, Selection Criteria recommendations were developed to enable a holistic evaluation of vendors, considering not only raw performance but associated risks uniquely related to the clinical deployment of AI. In-house experience and key bodies of work on ethics, standards, and best practices for AI in Radiation Oncology were reviewed to inform selection criteria and evaluation strategies. A retrospective analysis using the criteria was performed across six vendors, including a quantitative assessment using five metrics (Dice, Hausdorff Distance, Average Surface Distance, Surface Dice, Added Path Length) across 20 head and neck, 20 thoracic, and 19 male pelvis patients for AI models as of March 2023. A total of 47 selection criteria were identified across seven categories. A retrospective analysis showed that overall no vendor performed exceedingly well, with systematically poor performance in Data Security & Responsibility, Vendor Support Tools, and Transparency & Ethics. In terms of raw performance, vendors varied widely from excellent to poor. As new regulations come into force and the scope of AI auto-segmentation systems adapt to clinical needs, continued interest in ensuring safe, fair, and transparent AI will persist. The selection and evaluation framework provided herein aims to promote user confidence by exploring the breadth of clinically relevant factors to support informed decision-making.

Combined synoptic and regional weather patterns affecting atmospheric Poaceae pollen concentrations in Sydney, Australia - Charlotte M. Waudby; Steven C. Sherwood; Nicholas J. Osborne; Paul J. Beggs; Jane Al-Kouba; Elizabeth E. Ebert; David J. Muscatello (Aerobiologia, 2022)
Inhalation of grass pollen can result in acute exacerbation of asthma, prompting questions about how grass pollen reaches metropolitan areas. We establish typical atmospheric Poaceae (grass) pollen concentrations recorded at two pollen samplers within the Sydney basin in eastern Australia and analyse their correlation with each other and meteorological variables. We determine the effect of synoptic and regional airflow on Poaceae pollen transport during a period of extreme (≥ 100 grains m −3 air) concentration and characterise the meteorology. Finally, we tested the hypothesis that most Poaceae pollen captured by the pollen samplers originated from local sources. Fifteen months of daily pollen data, three days of hourly atmospheric Poaceae pollen concentrations and fifteen months of hourly meteorology from two locations within the Sydney basin were used. Weather Research Forecasting (WRF), Hybrid Single-Particle Lagrangian Integrated Trajectory (HYSPLIT) modelling and conditional bivariate probability functions (CBPF) were used to assess Poaceae pollen transport. Most Poaceae pollen collected was estimated to be from local sources under low wind speeds. Extreme daily Poaceae pollen concentrations were rare, and there was no strong evidence to support long-distance Poaceae pollen transport into the Sydney basin or across the greater Sydney metropolitan area. Daily average pollen concentrations mask sudden increases in atmospheric Poaceae pollen, which may put a significant and sudden strain on the healthcare system. Mapping of Poaceae pollen sources within Sydney and accurate prediction of pollen concentrations are the first steps to an advanced warning system necessary to pre-empt the healthcare resources needed during pollen season.

Ghosts of the deep – Biodiversity, fisheries, and extinction risk of ghost sharks - Brittany Finucci; Jessica Cheok; David A. Ebert; Katelyn Herman; Peter M. Kyne; Nicholas K. Dulvy (Fish and Fisheries, 2021)
Ghost sharks (subclass Holocephali) remain a largely data‐poor group of cartilaginous fishes. The general paucity of attention may partially be related to identification and unresolved taxonomic issues, occurrence in the deep oceans, and their low value and interest in fisheries (which some notable exceptions). Here, we synthesize and assess the extinction risk of all known extant ghost sharks (52 species) by applying the IUCN Red List of Threatened Species Categories and Criteria. Ghost sharks have a low proportion of threatened (8%) and Near Threatened (8%) species, with most species (69%) assessed as Least Concern. The group still exhibits some data deficiency (15%), and biological information is lacking for most species. Endemism is high, with 37% of species known from only one location or one country. Species richness was highest in the Northeast Atlantic, off the northwest coast of Africa (Morocco to Mauritania), the East China Sea, New Zealand and off the northwest coast of South America (Ecuador and Peru). Ghost sharks are predominately taken as by‐catch, but some targeted fishing and/or retention for the liver oil trade occurs. Species‐specific reporting, monitoring and management are required to assess population trends, and further investigation is needed on trade and use, particularly for higher risk species including the sicklefin chimaeras (genus Neoharriotta ) and the American Elephantfish ( Callorhynchus callorhynchus , Callorhinidae).

Troubled waters: Threats and extinction risk of the sharks, rays and chimaeras of the Arabian Sea and adjacent waters - Rima W. Jabado; Peter M. Kyne; Riley A. Pollom; David A. Ebert; Colin A. Simpfendorfer; Gina M. Ralph; Shaikha S. Al Dhaheri; K. V. Akhilesh; Khadeeja Ali; Mohamud Hassan Ali; Tariq M. S. Al Mamari; K. K. Bineesh; et al. (Fish and Fisheries, 2018)
The extinction risk of sharks, rays and chimaeras is higher than that for most other vertebrates due to low intrinsic population growth rates of many species and the fishing intensity they face. The Arabian Sea and adjacent waters border some of the most important chondrichthyan fishing and trading nations globally, yet there has been no previous attempt to assess the conservation status of species occurring here. Using IUCN Red List of Threatened Species Categories and Criteria and their guidelines for application at the regional level, we present the first assessment of extinction risk for 153 species of sharks, rays and chimaeras. Results indicate that this region, home to 15% of described chondrichthyans including 30 endemic species, has some of the most threatened chondrichthyan populations in the world. Seventy‐eight species (50.9%) were assessed as threatened (Critically Endangered, Endangered or Vulnerable), and 27 species (17.6%) as Near Threatened. Twenty‐nine species (19%) were Data Deficient with insufficient information to assess their status. Chondrichthyan populations have significantly declined due to largely uncontrolled and unregulated fisheries combined with habitat degradation. Further, there is limited political will and national and regional capacities to assess, manage, conserve or rebuild stocks. Outside the few deepsea locations that are lightly exploited, the prognosis for the recovery of most species is poor in the near‐absence of management. Concerted national and regional management measures are urgently needed to ensure extinctions are avoided, the sustainability of more productive species is secured, and to avoid the continued thinning of the regional food security portfolio.